(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article considers the expression of the historical progress of mankind in the genres of fine art. In particular, it is possible to study historical information about the way of life of people, means of labor, historical events, nature. In turn, the article analyzes the role of works of fine art in the formation of the anthropological worldview and spirituality of man.